Al-Tasybih fi al-Akhadis al-Nabawiyyah min Kitab “al-Lu’lu’ wa al-Marjan fima Ittafaqa ‘alaihi al-Syaikhon” - Ulum, Fatkhul; Munir, Munir; Kasim, Amrah (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research aims to determine the types of adat al-Syibhi, the differences and the roles in understanding the texts of the hadith of the Prophet, as well as facilitating the identification of tasybih elements in a hadith text. This research is a Library Research, that relies on a descriptive analytical approach (al-Manhaj al-Washfi al-Tahlili). Descriptive approach is to analyze scientific material that is related to the subject, through library research and then presented and explained systematically. The analytical approach is to analyze the hadith of the Prophet which contains the aspects of tasybih and the words of the ‘ulama (clerics) and balaghah experts. Adat al-Shibh is the link between musyabbah and musyabbah bih. Tasybih will not be considered as completed without adat al-Syibh. Adat al-Syibh has a big role in tasybih, which can be mentioned in the sentence or omitted, and with omitting, it will give a stronger meaning than mentioning. Tasybih in terms of the Adat of al-Sibh is divided into two, namely the tasybih mursal, if its adat al-syibh is mentioned and tasybih muakkad if its adat syibih is omitted. Adat al-Syibh in the hadith uses four kinds of kaf, kaanna, mislu, and nahwu. This research confirms the ability of bayan nabawi to describe abstract meanings and thoughts, especially something that is related to occultism, which the meaning is transformed into a motion picture, because something visible and concrete can strengthen meaning and can give a greater influence in heart and mind.